57 Channels (And Nothin On) - Does TV-News on the Eurozone Affect Government Bond Yield Spreads? - Julia Wolfinger; Lars P. Feld; Ekkehard A. Köhler; Tobias Thomas (Center for Economic Studies and ifo Institute (CESifo), 2018)
This paper empirically investigates the relationship between TV news coverage and the GIIPS countries' bond yield spreads using daily data between January 1, 2007 and December 1, 2016. We employ 1,542,233 human coded news items from evening news shows of leading TV stations in 12 countries which include 37,859 news on the EU, on the Eurozone and on country-specific economic issues. We find that an increasing share of news about the Eurozone reduces yield spreads, especially when the news has a positive tonality. This hints at the effectiveness of political communication through the media by European institutions and in particular the European Central Bank (ECB). In conjunction with the tonality of the news, we find that country-specific news have a significant impact on GIIPS yield spreads. A higher share of positive/negative news is positively associated with a decrease/increase of the GIIPS yield spreads vis-à-vis Germany. Moreover, some news is not immediately and completely priced in by market participants when it is released. In addition, this peculiar effect of country specific news is stronger when the respective news is aired on the North American media market.
Keywords: E58; G12; L80; N14; 330; Eurozone; Euro; political communication; media coverage; yield spreads; dynamic macro panel; FGLS